Students' Decision Steps in Meta-Cognitive Learning in Free Online Groups (MetaL-FrOG): A Case Study - Sen Fa, Kinsley Ng; Hussin, Firuz Hussin (The Turkish online journal of distance education TOJDE, 2011)
What prompts the students to respond in online dialogic discussion? Why some students chose to fall out? This case study through the lens of phenomenography observation attempts to explain the five decision steps of students to respond in Meta-cognitive Learning in Free Online Groups (MetaL-FrOG) discussion. It presents a part of a research project by the name of Triarchy Perspective on Meta-cognitive Learning in Free Online Groups. The research setting was online learner community on the platform of Free Online Group web intended for post-graduate students enrolled for the paper Psychology of Learning in Faculty of Education, University Malaya, Malaysia. Preliminary study revealed three factors contributed to MetaL-FrOG success: Motivation, Cognitive Resources and Pro-learning Behaviors. This paper only presents a part of the findings under the Pro-Learning Behaviors Sub-theory. We found striking similarities between the model proposed by Latane & Darley (1971), Five Essential Steps to a Pro-social Response in an Emergency, and our research subject. The model which explains the course of a pro-social decision was borrowed and modified as surrogate theory to explain the online discussion response of the students. The insights help educators to better understand what holds students back from fruitful online peer diologic discussion. (Contains 3 figures.)